Pentingnya Peran Pembinaan Bagi Kehidupan Lansia - Selviana Putri Naibaho; Eni Marlina Sihombing; Megawati Manullang (Institut Nalanda, 2024)
Elderly is the final stage and period when a person reaches the age of 60 years and above. One of the characteristics of the elderly is physical and mental decline. At this time the ederly really need attention from the servants and mentors who accompany them in living life. The purpose of this coaching is to increase the enthusiasm and motivation of the elderly. Counseling for the elderly has a very important role in improving their quality of life. With proper guidance such as health programs, social activities, and skills training, the elderly can feel more empowered and involved in their daily lives. Coaching allows older adults to feel valued, which leads to psychological well-being. Not only can they gain new knowledge, but they can also build positive social relationships. Therefore, the role of the coach towards the elderly is very important. It also helps to create a supportive environment where the elderly feel valued and cared for. It therefore focuses not only on physical aspects, but also emotional and social well-being, to help the elderly live a more meaningful and happy old age. With the right approach, coaches can help older adults remain productive and contribute to society moving away from the confines of the home.